A circovirus-like genomic sequence with unique architecture and phylogenetic relatedness to human-linked viral lineages - Dai, Liyan; Mao, Lichen; Shi, Wenhui; Ndjekadom, Alfred; Wang, Xiaochun; Liu, Yuwei; Yang, Shixing; Ji, Likai; Wang, Jianqiang; Ma, Jin; Zhang, Wen; Shen, Quan (Frontiers in Cellular and Infection Microbiology, 2025)
Circoviruses are small viruses in the Circoviridae family that associate with a wide spectrum of disease from asymptomatic to lethal in different animal. In the current study, a novel swine-origin circovirus with unique genomic architecture was determined from both oropharyngeal swabs and fecal samples collected from febrile pigs in Jiangsu Province, China. The complete genome sequence of this novel porcine circovirus strain (named as PCV-CH-ZJ01) was determined to be 2544 nt in length, containing four major open reading frames: Rep1, 498–833 nt, 112 aa; Rep2, 1055–1546 nt, 164 aa; Cap1, 1756–2055 nt, 100 aa; Cap2, 2089–2529 nt, 147 aa. Comparative sequence analysis revealed differential conservation patterns across viral components and shared low amino acid similarity with other strains on the whole. Phylogenetic trees based the whole genome and amino acid of two Reps revealed that PCV-CH-ZJ01 belonged to circovirus and clustered with human and rhesus macaque circovirus strains, which raised the concerns of potential cross-species transmission between swine and human.